Elaboración y aplicación de guía didáctica con enfoque constructivista para el aprendizaje de trigonometría en los estudiantes de tercer semestre, de la escuela Ciencias Exactas, período Diciembre 2012 –Junio 2013 - Cruz Morocho, María Inés (2016)
It has been displayed over teaching experience that while it is true trigonometry as such is an important branch that involves understanding the issues surrounding us; but to students teachers have been using the traditional teaching method, where only the theoretical class is taught and exercises are solved on the board, as students sometimes learning and there are times that are empty in relation to understanding trigonometry. Bringing the student to get lost in the teaching-learning process giving rise to many negative effects not only in the process of teaching and learning but also on a personal level, producing a negative to study and understand trigonometry, the solution to this problem is the development and implementation of a tutorial with constructivist approach based on the syllabus of the third semester of exact sciences, one of the best strategies to ensure the acquisition of knowledge trigonometry. inductive methods, analytical and synthetic research was used for development; the type of research which was based and was based is diagnosed or proactive investigation thereof having a field design, literature. Further research is supported validation of instruments to collect information such as survey and questionnaire, same as applied to seventeen lords students which show that for the process of teaching and learning is complete, dynamic and fun to use the applying a tutorial with thematic contents according to the syllabus of the third semester trigonometry and its application in solving problems taking the active involvement of students completing the teaching process with meaningful learning.